THE DEVELOPMENT OF AFGHANISTAN’S POLITICAL SYSTEM: FROM KINGDOM TO TALIBAN RULE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the stages of formation and development of the Afghan political system, from the monarchy to the Taliban's rise to power. The article systematically covers the transition from monarchy to the Republic, state governance during the socialist regime, political chaos during the civil war, the system used by the United States for the Afghan people, and the Taliban government's efforts to gain power and rise to power.